Three intervention levels for improving smoking behavior among Royal Thai army conscripts - Pannee Pantaewan (2018)
We evaluated a smoking cessation program based on an ecological model among Royal Thai Army conscripts with three levels of behavioral change intervention: intrapersonal level, interpersonal level and organizational level. The program applied processes of change in the Transtheoretical Model for intervention at the intrapersonal level; social support from the family at the interpersonal level; strengthening policies and activities to support quitting, including providing a smoke-free workplace at the organizational level. Eighty-nine participants were purposively selected from the first regiment of conscripts at the King's Royal Guard, recruited into the Army in 2009. The behavioral change intervention was conducted during their first six months of duty. A self-administered questionnaire was used to collect data between May and November 2009. Individual interviews and checklist observations were employed to collect data. Data was analyzed using inferential statistics, comparing means by paired t-test and the chi-square test was used to analyze correlations. Qualitative data were analyzed thematically. Sixty-three percent of participants significantly (p < 0.001) reduced the number of cigarettes smoked, and 4.5% quit smoking. There was significant improvement in self-efficacy for improving smoking behavior (p=0.002) and making an effort to quit (p < 0.001).